Design and fabricate a gantry type of co2 laser cutting machine - Mohammad Rafiq, Radzuan (2012)
Now days, a flexible machining and precise positioning operation is typically refers to a gantry system that generate the idea to create a very own gantry type CO2 laser cutting machine. To design and fabricate this gantry machine, some fundamental studies had been carried out in terms of its suitability, versatility, ergonomically and economical with provided budget. Comparison between other designs is needed to make sure it fulfils all the criteria. This project involves the process of designing the gantry machine considering to economic and ergonomic factor for people to use. After all the process, the machine had been successfully developed within light budget of RM 10,000 and successfully tested to prove its operation.